CYSTS OF THE CENTRAL NERVOUS SYSTEM: A REVIEW OF 35 CASES WITH OUTCOMES - SURENDER; NEERAV PORWAL; SAPNA CHAUHAN; ASHOK KUMAR4 (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Non-neoplastic, non-inflammatory cysts of the central nervous system (CNS) may cause symptoms as a result of changes in pressure, rupture or secondary inflammation. The cyst-related details, such as its age, site, cyst wall, and its contents, also provide an insight into their embryology and histogenesis. This paper reviews the clinic-pathological features of cysts of CNS. Methods: In this study, a prospective analysis of the cysts of CNS diagnosed between November 2019 and October 2023 who presented to our outpatient department and managed at Command Hospital Lucknow and Base Hospital Delhi Cantt were reviewed. Written informed consent was taken from all patients. Cystic degeneration in tumors or inflammatory lesions was excluded from the study. Results: There were 35 cysts in the study period of 04 years. Majority of intracranial cysts presented with signs of raised intracranial pressure. Patients with epidermoid cysts had additional cerebellar signs, visual disturbances and deafness. Cord compression is the main presentation of all spinal cysts. Conclusion: Cysts of CNS are usually maldevelopment in nature. A few are acquired. The radiological identification of these cysts and pathological confirmation is necessary for prognostic purposes.